The Influence of Mass Media on Public Perception of Criminal Cases: A Qualitative Approach - Fadhilah, Nurul (Journal of Strafvordering Indonesian, 2024)
The mass media plays a pivotal role in shaping public perceptions of criminal cases, influencing how individuals understand and respond to legal issues. This study explores the influence of mass media on public perceptions of criminal cases through a qualitative approach, utilizing in-depth interviews and media content analysis. It investigates how media framing and narratives shape public opinion, as well as the role of the media in shaping legal awareness and social justice. The study reveals that media framing often leads to bias and stereotyping, impacting public views of perpetrators and victims. Moreover, consumption of news without verification can increase fear and anxiety in communities. Media practitioners and law enforcement professionals feel pressure to produce sensationalized news, compromising accuracy and balance. Despite the potential of mass media to enhance legal literacy, its effectiveness depends on ethical news coverage and media literacy education. Collaboration between media and law enforcement is crucial to ensure information dissemination does not disrupt the judicial process. In conclusion, responsible media coverage is essential for fostering a fair and transparent judicial system, and this study offers insights for improving media practices and promoting justice in society.